1, 2, 4, 5-Dioxadiazine-functionalized [N–NO2]− furazan energetic salts. Issue 39 (6th September 2016) - Huang, Haifeng; Shi, Yameng; Liu, Yanfang; Yang, Jun
Abstract : 1, 2, 4, 5-Dioxadiazine is identified as a key bridge to improve the density and detonation performance of energetic materials. Abstract : The 1, 2, 4, 5-dioxadiazine ring was introduced as a bridge connecting two nitraminofurazan moieties to form energetic salts based on 3, 6-bis(4-nitramino-1, 2, 5-oxadiazol-3-yl)-1, 2, 4, 5-dioxadiazine (H2 BNOD). Eight nitrogen-rich energetic salts based on the BNOD anion were synthesized and fully characterized by NMR ( 1 H NMR, 13 C NMR, 15 N NMR), IR and elemental analysis. Furthermore, H2 BNOF (5 ), ammonium (6 ), hydroxylammonium (8 ) and 4-amino-1, 2, 4-triazolium salts (13 ) were analyzed by single-crystal X-ray diffraction. The densities of the salts were in the range of 1.730 (13 ) to 1.914 g cm −3 (8 ). These salts showed much better thermal stabilities and mechanical sensitivities than their precursor, H2 BNOD. The decomposition temperatures of the salts ranged from 114 (6 ) to 197 °C (9 ). The impact sensitivities of the energetic salts were between 1.5 and 4.5 J, and their friction sensitivities ranged from 53 to >144 N. Their detonation pressures and detonation velocities were calculated to be in the range of 26.3 (12 ) to 38.1 GPa (8 ), and 7754 (12 ) to 9095 m s −1 (8 ), respectively.